(untitled) (Indian Journal of Engineering and Materials Sciences (IJEMS), 2024)
In the era of mass customization material selection for biomedical and other engineering applications has become extremely sensitive under requirement perspective. With the advent of new technologies, exotic materials with diverse features are coming up for various applications. It becomes a concern for biomedical and other professionals to select the best material for the purpose. This paper proposes a new model combining analytic hierarchy process (AHP) and multi attribute boarder approximation area comparison (MABAC) method under the environment of rough set. Rough numbers have been used to capture and aggregate the perception of decision makers in vague and imprecise environment. To establish the usefulness of the proposed method, material selection problems for making of hip joint prosthesis, fuel cell, product working at elevated temperature and a sailing boat mast have been illustrated. Comparative analysis and validation of results with published literatures prove the efficacy of the proposed method.